Integrating Industry 4.0 in Higher Education Using Challenge-Based Learning: An Intervention in Operations Management - Eliseo Vilalta-Perdomo; Rosario Michel-Villarreal; Ricardo Thierry-Aguilera (MDPI AG, 2022)
Industry 4.0 is predicted to significantly transform the jobs and skill profiles of workers. Implications for higher education may involve dramatic changes in the demand for knowledge and skills. In response to this, a Challenge-Based Learning (CBL) intervention was designed with the aim of developing working skills for the future of work on undergraduate students by embedding the Industry 4.0 theme in the Operations Management curricula. The CBL intervention was implemented in two different academic terms at a UK university, and views from 302 undergraduate business students were captured using document analysis. The benefits are reported in terms of knowledge acquisition and the application and development of key desirable working abilities for the future. The results suggest that CBL increases students' understanding of Industry 4.0 issues in real-life settings. It also provides an environment for soft-skills training for skills, including collaboration, communication, planning and problem-solving. This study provides a blueprint for the implementation of CBL in the Operations Management curricula. The study validates existing findings obtained from the application of CBL in other disciplines. Whilst the proposed CBL intervention might be easily replicated in business schools in the UK, the findings on students' experiences might not be directly generalized to other contexts or disciplines.